The impact of tax burden on welfare attitudes: Micro evidence from welfare states. - Yinan Guo; Ting Gong (PLoS ONE)
The attitudes of the general public with regard to social welfare are of crucial importance in determining the efficacy and stability of a nation's welfare system. The manner in which taxation is employed as a means of funding mechanism for welfare policies is of great consequence. Nevertheless, existing research on the subject of welfare attitudes has largely neglected the tax perspective, underscoring the need for investigations that bridge this gap and provide a more comprehensive understanding of the intertwined dynamics between taxation and public perception of social benefits. This study investigates the influence of tax burdens on attitudes towards welfare using an ordered probit model applied to data from the 2019 International Social Survey Program (ISSP 2019 Social Inequality V), encompassing 11 welfare states. Our key findings are as follows: (1) Empirical analysis reveals that a moderate tax burden correlates with a reduction in public expectations regarding governmental responsibility for welfare provision. (2) Heterogeneity analysis elucidates a negative association between tax burdens and welfare attitudes across diverse welfare regimes. (3) The mediating effect test suggests that perceptions of social fairness partially mediate the relationship between tax burdens and welfare attitudes. (4) The moderating effect test indicates that government efficacy negatively moderates the impact of tax burden on welfare attitudes. This study offers insightful perspectives for policymakers aiming to design and implement tax systems that align effectively with societal structures.